Algorytmy do wyznaczania amplitudy sygnału sinusoidalnego z zastosowaniem wybranego estymatora częstotliwości = Algorithms for determining the sinusoid signal amplitude with the use of a selected frequency estimator - Krajewski, Mariusz; Sienkowski, Sergiusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents a comparison of metrological properties of known and latest algorithms for determining the amplitude of a sinusoidal signal in cooperation with a frequency estimator. Least squares (LS), Total Least Squares (TLS) algorithms and four DFT-based frequency domain algorithms, including one recursive, were analyzed. The results of simulation tests showed that in the case of sinusoidal signal with Gaussian noise, the most accurate algorithms are TLS and LS.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne